Responsibility, Representation and Participation: Bureaucratic Steering of Biofuel Research. (July 2020) - Shahare, Mahendra; Thayyil, Naveen
This article seeks to trace the implicit notion of responsibility in the bureaucratic steering of biofuel research in India—as a useful entry point to think further on framework of Responsible Research and Innovation (RRI) in India. It concentrates on a specific aspect within the RRI framework in particular—public engagement and concerns for greater participation. By engaging with R&D in biofuel technologies in India, the techno-bureaucratic steering of its trajectories and the emphasis on public engagement within RRI frames, this article seeks to bring focus on how S&T governance in India could in principle be made more responsive to societal needs by motivating positive developments in line with public needs.